Throttle Valve as a Heating Element in Wind Hydraulic Thermal System - Mujtaba, Muhammad; Cuntang, Wang; Yasin, Faisal Muhammad; Xie, Fangwei (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2018)
A new energy conversion system is established which converts wind hydraulic energy directly to heat energy. For this purpose of conversion throttle valve considered as a heat generating source in the utilization ofwind energy to confine the wind energy into thermal energy. The use of throttle valve indicates to calculate the heat generation by using the simulation in Matlab and count the physical and mathematical model of the heating system. Various analyses are made on the basis of throttle valve parameters to compare the theoretical results on various values. To compute the effective results, needle valve used as a testing element in hydraulic system to change the opening of the throttle valve which estimates the heat generating capacity of the system. The opening degree and angle of the throttle valve are analyzed theoretically under the condition of constant flow rate. The effect of stiffness and other parameters on the heating system analyzed at the same time. The results show that the valve opening is responsible for the generation of the heat as more heat can be achieved in case of the small opening. Another analysis is made that the angle changed on throttle tip significantly affects the heat effect of the throttle valve. To ensure the stability of the system the stiffness of the throttle valve will be more conductive to ensuring a constant pressure across the valve port. The Matlab software is used to build a mathematical model for a proper analysis on throttle valve on various openings to check the pressure drop relationship with different parameters.